Political prioritisation for performance-based financing at the county level in Kenya: 2015 to 2018 - Waithaka, D; Gilson, L; Barasa, E; Tsofa, B; Orgill, M (Kerman University of Medical Sciences, 2023)
Background: Performance-based financing (PBF) was introduced to Kilifi county in Kenya in 2015. This study investigates how and why political and bureaucratic actors at the local level in Kilifi county influenced the extent to which PBF was politically prioritised at the sub-national level.